Educação Transmídia: contribuições acerca da cultura da convergência em processos educacionais - Montanaro, Paulo Roberto (2016)
The present work aims to reflect on the different aspects about the new paradigms of communication and dialogue that are shaped by the transformations resulting from a social restructuring from the development of digital technologies of communication and information. The proposal, therefore, is to understand how the concepts of the transmedia storytelling and the culture of convergence can become catalysts of mediation processes that consider the characteristics of ubiquity and social nomadism, as well as incorporate to teaching and learning strategies elements such as gamification of contents; Immersive technologies; Participatory culture of knowledge construction and other elements that have developed as a result of this new network society. Thus, in a bibliographical research that addresses issues of the field of education and communication, the research intends to elaborate a critical analysis on the different aspects of the use of digital technologies in education, prioritizing the dialogicity and the involvement between the different actors and contents, within strategies of transversal articulation between the different media. Divided into three parts, the work is initially intended to establish a context about the use of different digital communication technologies and languages derived from the particularities of each one of them. It then reflects on this social reconfiguration where, at the same time as we create and invent new ways of communicating ourselves and having access to information, we are transformed by each of these new tools and our relationship with the other and with the world It changes completely, and finally, as the concepts of the transmedia storytelling already widely studied in the fields of art, culture and entertainment can add value to the surrounding teaching and learning strategies.